Normobaric interval hypoxic training in the treatment of fractures of the trochanteric region of the femur - Shymon, Vasyl; Stojka, Vasil; Sheregyi, A.; Shymon, Mykhaylo; Slyvka, Roman (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Trochanteric fractures of the femur amount from 2 to 13.5 % of all fractures of bones and 28–37,5 % of femoral fractures, and unsatisfactory outcomes of their treatment — from 16 to 40 %. Negative impact on the outcome of the treatment have osteoporosis, immunosuppressive conditions associated with long-term therapy, hormonal therapy, diabetes and thyrotoxicosis. Objective: To improve outcomes of treatment and rehabilitation in patients with fractures of the trochanteric region of the femur by means of the method of normobaric interval hypoxic training (IHT) and to study its effect on bone metabolism. Methods: In the period from 2012 to 2015 at the Clinic of the Chair of general surgery UzhNU we treated trochanteric fractures of the femur in 34 patients. The first group included patients in which we performed IHT with gas mixture of 12 % oxygen; the second one consisted of patients with thyrotoxicosis who received similar treatment, the control group consisted of 7 patients with these fractures who renounced IHT. Patients were examined by a laboratory and clinical methods. Results: The best physical activity was observed in the patients of the first group. In the second group start physical activity was low but we observed its impetious development. In the control group physical activity comparing to the first two groups increased slowly. On follow-up examination after 1 month it was noted increasing of calcium level in the serum of all groups of patients but it was more in the second one. Phosphorus level decreased in the first and control groups, and it incresed in the second group. Levels of osteocalcin and alkaline phosphatase increased and what is more in the first two groups indeces were significantly higher comparing to the control group. Conclusions: Using of IHT leads to increasing in physical activity and contributes to the process of rehabilitation. After IHT one may observe an improvement of indeces of bone metabolism activity.